Optobiology: live cells in optics and photonics. (23rd November 2020) - Miccio, Lisa; Memmolo, Pasquale; Merola, Francesco; Mugnano, Martina; Ferraro, Pietro
Abstract: A new intriguing paradigm recently emerged in bio-photonics, in which a single biological element such as a simple cell can be used as an optical or photonic component having well-defined features. Based on this novel concept, the interactions between light and biological matter can be exploited in many circumstances as useful tools in various fields of science and technology. In fact, it is surprising as well as exciting that the optical behavior of living cells permits their use as microlenses for imaging, photonic microresonators or optical waveguides. Moreover, it has been demonstrated that biological cells can behave as advanced probes for optical tweezing, able to manipulate matter at the nanoscale and also as subwavelength probes of localized fluorescence. Here, we present an overview of these fascinating applications of biological lenses. The aim of the present Topical Review is to introduce a completely new scenario to the community of scientists working in optics and photonics. A developing research field is presented, in which live cells can be employed and exploited as optical components for incredible applications ranging from simple imaging, to manipulation of soft matter, to biomedical diagnosis. Several of the most significant studies and discoveries will be illustrated and discussed.